Systemic chemotherapy with doxorubicin, cisplatin and capecitabine for metastatic hepatocellular carcinoma - Bang Soo-Mee; Lee Jeong; Park Yeon; Kim Ju; Kim Sun; Kwon Oh; Kwon So; Han Sang; Lee Yuna; Park Se; Cho Eun; Shin Dong; et al. (BMC Cancer, 2006)
Abstract Background Although numerous chemotherapeutic agents have been tested, the role of systemic chemotherapy for hepatocellular carcinoma (HCC) has not been clarified. New therapeutic strategies are thus needed to improve outcomes, and we designed this study with new effective drug combination. Methods Twenty-nine patients with histologically-confirmed, metastatic HCC received a combination chemotherapy with doxorubicin 60 mg/m2 and cisplatin 60 mg/m2 on day 1, plus capecitabine 2000 mg/m2/day as an intermittent regimen of 2 weeks of treatment followed by a 1-week rest. Results The median age was 49 years (range, 32–64) and 19 patients were hepatitis B virus seropositive. Child-Pugh class was A in all patients and 4 had Zubrod performance status of 2. The objective response rate was 24% (95% CI 9–40) with 6 stable diseases. The chemotherapy was generally well tolerated despite one treatment-related death. Conclusion Combination chemotherapy with doxorubicin, cisplatin and capecitabine produced modest antitumor activity with tolerable adverse effects in patients with metastatic HCC.